2020
DOI: 10.1039/d0qi00779j
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive light-emitting metal complexes and related materials

Abstract: Thermo-responsive light-emitting materials have wide potential applications in temperature sensing, bioimaging, optoelectronic devices and information security, due to their intriguing luminescent property changes in response to temperature. Among them, light-emitting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…However, for a quantitative analysis, the detection of luminescence changes allows for much higher sensitivity and lower signal interferences than color detection. These kinds of molecular probes and materials [201][202][203] are widely studied and suitable for different applications (e.g., temperature sensing, optoelectronic devices, and anticounterfeiting technologies [204] ); however the literature on thermochromic/thermoluminescent electrospun nanofibers is not too vast if compared to the research carried out on bulk materials having the same characteristics. [201,205] In this frame, the processing of the materials into electrospun nanofibers presents further significative advantages, such as very high surface area and porosity, which are extremely attractive characteristics when it comes to the preparation of high-performance sensors.…”
Section: Thermo-optically Responsive Electrospun Fibersmentioning
confidence: 99%
“…However, for a quantitative analysis, the detection of luminescence changes allows for much higher sensitivity and lower signal interferences than color detection. These kinds of molecular probes and materials [201][202][203] are widely studied and suitable for different applications (e.g., temperature sensing, optoelectronic devices, and anticounterfeiting technologies [204] ); however the literature on thermochromic/thermoluminescent electrospun nanofibers is not too vast if compared to the research carried out on bulk materials having the same characteristics. [201,205] In this frame, the processing of the materials into electrospun nanofibers presents further significative advantages, such as very high surface area and porosity, which are extremely attractive characteristics when it comes to the preparation of high-performance sensors.…”
Section: Thermo-optically Responsive Electrospun Fibersmentioning
confidence: 99%
“…This phenomenon can be attributed to a change in the molecular or crystal structure. 118,119 Both compounds 3a and 3b crystallize either as colourless, blue-emitting crystals or as yellow, green emitting crystals. Interestingly, the colourless crystals of 3a and 3b are isostructural (Fig.…”
Section: Purely Cationic Chain Linksmentioning
confidence: 99%
“…[1][2][3][4] In particular, high photoluminescence quantum yields (PLQYs) approaching 100% are possible for the Cu(I) complexes as no internal quenching processes of excited states via low-lying metal-centered d-d* states take place in contrast to other 3d element (Ru II , Pt II and Ir III ) compounds. [5][6][7] Previous reports have indicated that Cu(I)-based complexes with different types of coordinated ligands are able to achieve remarkable luminescence characteristics, including room temperature phosphorescence (RTP) and thermally activated delay fluorescence (TADF). [8][9][10][11][12] Such cuprous complexes show great potential for applications in optoelectronic devices and luminescencebased sensors.…”
Section: Introductionmentioning
confidence: 99%